Development of E-LKPD Using POE-Based Liveworksheets on Acid-Base Concept - Vegha Dwi Arthamena; Lenny Anwar; Rasmiwetti Rasmiwetti (Hydrogen: Jurnal Kependidikan Kimia, 2023)
The purpose of this study was to develop an electronic worksheet (E-LKPD) based on the POE-based Live worksheet concept for the acid-base topic. The Plomp model research and development (R&D) design was employed in this research. The validity of the E-LKPD was assessed through validation sheets and user response questionnaires. Results of the validation conducted by three experts indicated that the E-LKPD was deemed valid for both material and media aspects, with average scores of 97.25% and 95.14%, respectively. Additionally, students and chemistry teachers had positive responses to the E-LKPD, with average scores of 82.33% and 88.89%, respectively. These results suggest that the developed E-LKPD is a feasible tool for learning.